2009
DOI: 10.1038/leu.2008.380
|View full text |Cite
|
Sign up to set email alerts
|

The novel immunosuppressive enzyme IL4I1 is expressed by neoplastic cells of several B-cell lymphomas and by tumor-associated macrophages

Abstract: We previously reported a strong IL4I1 gene expression in primary mediastinal B-cell lymphoma (PMBL) and recently identified the protein as a secreted L-phenylalanine oxidase, physiologically expressed by myeloid cells, which inhibits T-cell proliferation in vitro. Here, we analyzed the pattern of IL4I1 protein expression in 315 human lymphoid and nonlymphoid malignancies. Besides PMBL, IL4I1 expression in tumors was very frequent. IL4I1 was detected in tumorassociated macrophages from most of the tumors and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 26 publications
7
98
0
Order By: Relevance
“…The overexpression of IL-4 within FL microenvironment was thus associated to a strong activation of malignant B cells. In agreement, we observed that both IL4I1 and HOXC4, two previously described IL-4 target genes, 21,23 belonged to the 886-PS FL_B list (Supplementary Figure S3A). Similarly, GCET2/HGAL, another gene reported as induced by IL-4 in normal B cells and in some malignant B-cell lines, 24 was significantly upregulated in FL_B compartment (Supplementary Figure S3B) even if it was excluded from the microarray analysis by the initial standard deviation-based filtering.…”
Section: Il-4 Is Upregulated In Fl and Promotes Malignant B Cell Actisupporting
confidence: 69%
See 1 more Smart Citation
“…The overexpression of IL-4 within FL microenvironment was thus associated to a strong activation of malignant B cells. In agreement, we observed that both IL4I1 and HOXC4, two previously described IL-4 target genes, 21,23 belonged to the 886-PS FL_B list (Supplementary Figure S3A). Similarly, GCET2/HGAL, another gene reported as induced by IL-4 in normal B cells and in some malignant B-cell lines, 24 was significantly upregulated in FL_B compartment (Supplementary Figure S3B) even if it was excluded from the microarray analysis by the initial standard deviation-based filtering.…”
Section: Il-4 Is Upregulated In Fl and Promotes Malignant B Cell Actisupporting
confidence: 69%
“…21 Briefly, after appropriate antigen retrieval with microwave heating in high pH Target Retrieval Solution (DakoCytomation, Glostrup, Denmark), deparaffinized tissue sections were stained with anti-P-STAT6/Tyr641 antibody (polyclonal rabbit; dilution 1/30; Cell Signaling Technology, Danvers, MA, USA), using an indirect immunoperoxidase method (ImmPRESS anti-rabbit; Vector Laboratories, Burlingame, CA, USA) and diaminobenzidine (Vector Laboratories) as chromogen. For double immunostaining, slides were first incubated with anti-CD20 (clone L26, Dako), anti-CD5 (clone 4C7, Novocastra, Newcastle, UK) or anti-PD1 (clone NAT, Abcam, Cambridge, UK) monoclonal antibody and labeled using the alkaline phosphatase-conjugated avidin biotinylated enzyme complex procedure (Vector Laboratories).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…26,49 Recently, BCR inhibitors have gained considerable interest because of their effectiveness in several B-cell lymphoma subtypes. Interestingly, their efficacy relies not only on the direct blockade of BCR-mediated B-cell survival but also on their capacity to abrogate the BCR-dependent activation of integrins and increase of chemotaxis.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, high levels of the chemokine receptor CCR1 transcript, known to be an activation marker for monocytes, were found to be associated with a poor outcome in follicular lymphoma [14]. By contrast, the IL4I protein encoding secreted L-phenylalanine oxidase, which inhibits T-cell proliferation in vitro, was also found to be expressed in follicular lymphoma macrophages, where it may be associated with favorable features [15]. Using a microarray approach, the scavenger macrophage receptor with collagenous structure (MARCO), together with EPHA-1, a tyrosine kinase involved in transepithelial migration (expressed in granulocytes), and the transcription factor SMAD-1 (expressed in vascular endothelium) were suggested as prognostic markers in follicular lymphoma [16]: low SMAD-1 and MARCO expression were associated with better progression-free survival in a small patient cohort receiving chemotherapy and rituximab.…”
Section: Macrophages and Dendritic Cells In B-nhl Pathogenesismentioning
confidence: 83%